Civil Society Participation in European and Global Governance
XVII, 244 p.
Keywords: It is often argued that the enhanced consultation of civil society contributes to the democratization of European and global governance. This collection investigates whether this theoretical argument is supported by empirical evidence. Ten original essays analyze current patterns of civil society consultation in 32 intergovernmental organizations.